“Se eu te contar, você não conta para ninguém?”: compreensão dos efeitos da violação de segredos em crianças de 6 a 8 anos - Martins, Ana Luiza Colleoni (Universidade Federal de São Carlos, 2026)
Secrets play a fundamental role in social relationships, contributing to the strengthening of interpersonal bonds and to the formation of networks of allies. Although children develop the ability to keep secrets at an early age, their understanding of the social impacts of maintaining or violating the implicit agreements inherent to secrets remains underexplored. The present study investigated children’s understanding of the effects of secrets disclosure, taking into consideration two factors: (a) the degree of closeness between the secret holder and the confidant (friends vs. non-friends) and (b) the severity of the consequences associated with secret´s violation (harmless vs. serious). Participants were 46 typically developing children recruited from a school in the state of São Paulo, Brazil, divided into two age groups: 6–7 years (Mage = 6 years, 4 months; DP = 3.67 months) and 7–8 years (Mage = 7 years, 3 months, DP = 3.54 months). Participants were randomly assigned to one of two conditions: in Condition 1, the secret holder and the confidant were friends, whereas in Condition 2, they were not friends. Children from all conditions watched animated videos and used a Likert scale (ranging from 1 to 5 points) to evaluate the level of closeness between the characters after being exposed to situations in which a secret was either kept or disclosed to a third party. Analyses revealed that neither age nor gender influenced children’s evaluations of interpersonal closeness. A Wilcoxon signed rank test revealed significant differences in proximity level attributed at base line and after story telling: in C1 (Z = -3,92, p < 0,001) and in C2 (Z = -3,84, p < 0,001). Across conditions, children gave significantly lower closeness ratings following stories in which secrets were violated (M = 3,74; DP= 1,74) and higher ratings following stories in which secrets were kept (M = 8,13; DP= 1,68). Furthermore, violations involving serious consequences resulted in lower closeness ratings than violations involving harmless consequences, Z = -2,11, p = 0,04, r = 0,31. Together, the findings indicate that children are sensitive both to breaches of confidentiality and to the severity of their consequences, based on the content of the confidential information. These results suggest that 6- to 8-year-old children understand the important role of keeping secrets in interpersonal relationships.
"If I tell you, promise not to tell anyone?": understanding of the effects of violating secrets in 6- to 8-year-old children
Keywords: Segredos; Cognição social; Crianças escolares; Secrets; Social cognition; School aged children; CIENCIAS HUMANAS::PSICOLOGIA; 4. Educação de Qualidade